Integrating Islamic Business Ethics And Digital Transformation To Enhance Msme Competitiveness - Nur Alifah; Agus Rohmat Hidayat (Journal of Sharia Micro Enterprise and Cooperation, 2026)
Background: The convergence of Islamic business ethics and digital transformation represents a critical but underexplored determinant of Micro, Small, and Medium Enterprise (MSME) competitiveness in Muslim-majority economies. Objective: This study investigates the individual and interactive effects of Islamic business ethics and digital transformation on MSME competitiveness in Indonesia. Method: Using a quantitative approach with moderated multiple regression analysis, data were collected from 215 MSME owners/managers across five Indonesian provinces through stratified random sampling.Results: Islamic business ethics (β = 0.387, p < 0.001) and digital transformation (β = 0.341, p < 0.001) each significantly and positively affect competitiveness. Their interaction term is also significant (β = 0.148, p = 0.002), indicating a synergistic moderating effect. The integrated model explains 64.1% of variance in competitiveness.Conclusion: MSMEs that simultaneously embed Islamic ethical principles and embrace digital transformation achieve superior and more sustainable competitiveness. Policymakers should design integrated halal-digital ecosystem programs, while sharia financial institutions should expand ethics-based digital literacy support for MSMEs.